Consumer Preferences and Marketing of Ready-To-Eat Meat Products in Thrissur City of Kerala - Abraham, John; R., Senthil Kumar (International Journal of Livestock Research, 2021)
A study was carried out in Thrissur city of Kerala state to analyse the market potential and consumers preferred attributes towards ready-to-eat meat products, so as to formulate an effective marketing mix. A well-structured questionnaire consisting of 21 questions was applied among 112 randomly selected respondents and their responses were recorded. The study on consumer preferences was based on 17 product attributes and 12 brand attributes. The significant product attribute and brand attributes were found to be almost similar. A correlation study was performed to elucidate the relationship between the consumption of meat and meat products and the respondent’s attributes such as age, gender, income and education. A functional analysis disclosed a statistically significant relationship between the consumption of meat and meat products and the respondent’s age, gender, income and education. The analysis on the perception of respondents about ready-to- eat meat products revealed huge market potential owing to rising income and changing lifestyle. But effective market permeation has to be achieved through appropriate marketing mix of products and brand attributes. Consumer awareness and sales promotion through mass media has to be taken up on a large scale to carve a niche for ready-to-eat meat products among the consumers.